CONFRONTING IDENTITIES IN THE BALKANS AS A SECURITY CHALLENGE - Subotic, Milovan (The Policy of National Security, 2025)
Identity, whether national/ethnic, religious/confessional, or cultural, is one of the key determinants by which an individual or community defines who they are, what they are part of, and/or what they believe in. However, although identity determination plays a significant role in building community and fostering belonging, it can also become a source of instability, which is especially pronounced in multi-ethnic and multi-confessional societies. Tensions escalate when different identities are pitted against each other in a confrontational relationship and exploited for political manipulation. History is replete with examples in which differences in identity have triggered wars, mass suffering, and social divisions. If identity is presented as untouchable and monolithic, or when it is perceived as exclusive and unchangeable, it manifests itself as a primary factor of constant instability. The example of the dissolutive processes in the former Yugoslavia, from the beginning of the 90s, in the name of identity differences, is the most blatant one. The consequences of this antagonism persist today, in the third decade since the end of the complex conflicts in this region. The rhetoric of the 90s continues to contribute to radicalization, the strengthening of populism, and efforts to impose the identity policies of these countries as a top-tier political issue. Starting from the basic assumptions of identity as a confronting category, the paper analyzes the survival of conflict rhetoric in the former Yugoslavia, which is still based on “irreconcilable identity differences”, that is, what impact does the “truth” established in this way have on the political and security stability of the region.